Behavioral and Psychological Strategies of Long‐Term Weight Loss Maintainers in a Widely Available Weight Management Program. Issue 2 (23rd January 2020) - Phelan, Suzanne; Halfman, Tate; Pinto, Angela Marinilli; Foster, Gary D.
Abstract : Objective: The study's purpose was to use validated questionnaires to identify novel behavioral and psychological strategies among weight loss maintainers (WLMs) in a commercial weight management program. Methods: Participants were 4, 786 WLMs in WW (formerly Weight Watchers, New York, New York) who had maintained weight loss  ≥ 9.1 kg (24.7 kg/23.8% weight loss on average) for 3.3 years and had a current mean BMI of 27.6 kg/m 2 . A control group of 528 weight‐stable individuals with obesity had a mean BMI of 38.9 kg/m 2 and weight change  < 2.3 kg over the previous 5 years. Results: WLMs versus Controls practiced more frequent healthy dietary choices (3.3 vs. 1.9; η p 2  = 0.37), self‐monitoring (2.6 vs. 0.7; η p 2  = 0.30), and psychological coping (2.5 vs. 1.1; η p 2  = 0.25) strategies. WLMs also reported more willingness to ignore food cravings (4.4 vs. 3.5; η p 2  = 0.16) and had greater habit strength for healthy eating (5.3 vs. 3.2;  η p 2  = 0.21). Standard canonical coefficients indicated that dietary (0.52), self‐monitoring (0.40), and psychological (0.14) strategies as well as habit strength for healthy eating (0.15) contributed independently and most (49.5% of variance) to discriminating groups. Conclusions: In a widely available weight management program, more frequent practice of healthy dietary, self‐monitoring, and psychological coping strategies as well as development of greater habit strength for healthy eating differentiated long‐term WLMs from weight‐stable individuals with obesity.